Assessment of the Impact of Pre-Sowing Treatments on Variations in Seed Germination Dynamics and the initial Growth of Seedlings in Sterculia urens - Shirin, Fatima; Saudagar, Irshad Ali; Mohammad, Naseer; Soni, Rama; Tripathi, Kaushal; Prakash, Divya (Indian Forester, 2025)
This research highlights variation in seed germination parameters for seeds of vuinerabie forest tree species Sterculia urens, which produces gum karaya, a valuable non-timber forest product. Despite its economic significance, the conservation of S. urens faces challenges due to high demand and inadequate strategies. Various factors, including seed coat properties and environmental conditions, influence germination. This study emphasizes the importance of proper seed treatments, such as acid scarification with sulphuric acid, to enhance germination outcomes. Methodologically, the research categorized germination studies based on various germination parameters. Four seed lots from different populations were analyzed, revealing significant variations In seed morphometric traits, germination rates, and seedling growth. Notably, seeds from SU-CG-CMP exhibited the highest germination rates. Results showed that the final germination percentage varied among populations, with SU-CG-CMP reaching 97.50% success after a 20 min treatment. The germination dynamics Indicated that longer acid exposure correlated with higher rates, demonstrating the effectiveness of scarification in overcoming dormancy. Seedling growth was also assessed, revealing significant relationships between seed vigor and growth metrics. The study found that high vigor seeds produced healthier seedlings, highlighting the importance of seed quality in forestry.